Analisis Pengaruh Keterlibatan Pengguna, Dukungan Manajemen Puncak terhadap Kinerja Sistem Informasi Akuntansi - Diandra Oktafiandri; Nafala Maharani Pangesti; Dien Noviany Rahmatika, (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The use of a computerized accounting information system can help in the processing of company data so that from this data it will produce information that is useful for the company. This study uses a systematic approach to review the literature. The results of this research aim to determine the influence of formalization of system development, the involvement of AIS users, to provide real experience about the use of computerized information systems can help organize business information in such a way that it produces useful information for business. This study uses a systematic literature review. The results to find out the research aimed at the results of system development, the role of users of accounting information systems, analyze the impact of accounting system performance and the user's ability to work on projects, and provide empirical evidence. This research method uses the systematic review method (SLR) to analyze journals and articles. In addition, the purpose of this study is to determine the impact of user understanding level, peak management support, and user interest in performance. By analyzing journals and articles published between 2015 and 2024, the study focuses on the impact of key management systems that help users participate in the performance of accounting systems. Fifty journals are used as sources in this journal research. The impact of the accounting information system and the user's ability depends on the business's motivation for the process. This research method uses the systematic review method (SLR) to analyze journals and articles. In addition, the purpose of this study is to determine the impact of user understanding level, peak management support, and user interest in performance. An analysis of journals and articles published between 2015 and 2024, focusing on the influence of senior management on user participation in the performance of accounting systems, Fifty journals were used as sources in this journal study.